Comments on “A new deep-water Astyris species (Buccinoidea: Columbellidae) from the southeastern Pacific” by Araya et al. 2016 - Sellanes, Javier (Zootaxa, 2017)
The aim of this note is to clarify some aspects posed by Araya et al. (2016) in the description of the columbellid gastropod Astyris atacamensis for northern Chile, and also to complement it for providing further insight on important ecological aspects of the genus Astyris in the SE Pacific. Araya et al. (2016) fill an important gap, describing a species that in my opinion is important in many aspects, yet, they fail in connecting this new species with previous work in which this taxon has been mentioned. Araya et al. (2016) indicate that the genus has not been previously reported for the SE Pacific; however, Levin et al. (2002a) already mention finding Astyris permodesta (Dall, 1890) off Callao, Perú (~12°S). Astyris permodesta, originally described for the coast of California, is currently accepted under the genus Alia (Monsecour 2015). Although we still cannot confirm, most probably future analysis will prove that A. permodesta reported for Perú by Levin et al. (2002a) corresponds indeed to the new species Astyris atacamensis. Future work should elucidate the definitive placement of this species in either Alia or Astyris, but hereafter I will indistinctly use Astyris.